STUDYING INELASTIC TRANSVERSE ELECTRON SCATTERING FORM FACTORS OF THE ISOSCALAR TRANSITIONS IN 10B NUCLEUS - Al-qazaz, Ban (Iraqi Journal of Science, 2024)
The inelastic transverse electron scattering form factors are studied for the fourisoscalar transitions for the states of 10B nucleus. These states are specifiedby J T  =1+0 (0.718 MeV), 1 0 2 (2.154 MeV), 2+0 (3.587 MeV) and 3 0 2 (4.774MeV). These form factors are analyzed in the framework of the harmonic oscillatorshell model.The transverse form factors have been calculated in the framework of the multinucleonconfiguration mixing shell model using the two-body interaction of Cohenand Kurath (C-K) to generate the 1p-shell wave function. The core polarization (CP)effects are included in the calculations through effective g-factors. A higherconfiguration effect outside the 1p-shell model space enhances the form factors forq-values and reasonably reproduces the data. The value of the size parameter (b) ischosen to reproduce the root mean square charge radius. The present results arecompared with available experimental data and with that of other models.PACS:21.60-n,21.60 Cs, 25.30Dh,27.20 th